Seismology on Mars: An analysis of direct, reflected, and converted seismic body waves with implications for interior structure - Durán, C.; Khan, A.; Ceylan, S.; Zenhäusern, G.; Stähler, S.; Clinton, J.F.; Giardini, D. (Physics of the earth and planetary interiors, 2022)
The InSight (Interior Exploration using Seismic Investigations, Geodesy and Heat Transport) mission has been collecting high-quality seismic data on Mars since early 2019 that provide the first direct observations of its interior structure. Here we report on a complete analysis of the part of the marsquakes known as the low-frequency seismic events (main energy below 1 Hz) that are sensitive to the deep interior. To identify body-wave arrivals in the highly-scattered martian seismograms, we employ four complementary approaches: 1) time-domain envelopes; 2) polarised waveforms and their time-domain envelopes; 3) polarisation analysis; and 4) waveform matching. Through careful application of this processing scheme to each marsquake, we are able to significantly increase the number of phase picks relative to earlier analyses (from 41 to 76), including body-wave arrivals from direct (P and S), reflected (PP, SS, PPP, SSS, and ScS), and converted (Ps and Sp) phases. To constrain the depth of the marsquakes, we also identify depth phases (pP and sS). Following this, we invert an initial set of phase picks for models of interior structure, event distance, and depth, while predicting travel times for seismic phases not identified at the outset. Based on the predictions, we repick (every pick is subject to our processing scheme), thereby enlarging our differential travel-time data set (all picks are relative to the main P-wave arrival), and subsequently re-invert for an updated set of interior structure models, distances, and depths. Proceeding thus, we present updated radial seismic velocity models of the crust, mantle, and core. We observe crustal interfaces at average depths of 10, 25, and 45 km, respectively, of which the former two are interpreted as intra-crustal interfaces and the latter as the crust-mantle boundary. We find an upper mantle structure consistent with a low-velocity zone associated with a thermal lithosphere and a thermal gradient in the range 2.4–2.9 K/km that extends to a depth of ~450 km. The thermal structure of the Martian mantle indicates potential and core-mantle-boundary temperatures in the ranges 1650–1750 K and 1900–2100 K, respectively, implying an entirely liquid core at present. Based on the identification of ScS phases, we obtain an improved estimate of the Martian core radius (1820–1870 km) and mean core density (6–6.2 g/cm3). •We analyse low-frequency marsquakes for direct, reflected, and converted body waves.•We employ four complimentary processing methods to pick body waves consistently.•We significantly increase the number of reliable body-wave phase picks.•We determine updated models of seismic structure and location of marsquakes.•We find a thick lithosphere (~450 km) and a large core (~1820-1870 km in radius).